(untitled) (El-Wahat Journal for Research and Studies, 2025)
In This Study, We Search About The Spread Of Customary Marriage Culture In Simple Societies. We Also Try To Search For The Reasons For The Tendency Of Divorced Women To Customary Marriage. What Are The Psychological And Social Dimensions Of Customary Marriage Culture? What Is The Relationship Between Customary Marriage Culture And The High Rates Of Emotional Divorce? We Seek To Know Why Algerian Families Tend To Choose Emotional Divorce Without Resorting To Ending The Family Bond Through Irrevocable Divorce. Are They Afraid Of The Social Stigma Of Divorced Women? Or Is The Need To Maintain Family Harmony Necessitate , As Long As Children Are In Childhood? Since Customary Marriage Is A Taboo In Algerian Society, This Means That It Is Difficult To Reach The Respondents, As The Nature Of The Subject Requires Us To Search For Respondents Through The Snowball Method, With The Help Of Case Studies To Collect Data. These Procedures Are Supported By Qualitative Research In The Social Sciences. Through This Study, We Aim To Unveil The Psychological And Social Reasons That Push The Algerian Man To Customary Marriage And Accept Emotional Divorce, And When Women Accept Customary Marriage As An Alternative To Civil Marriage, Trying To Find Solutions And Suggestions That Contribute To Reducing The Phenomenon Of Emotional Divorce In Algerian Society Key Words: Customary Marriage Culture, Emotional Divorce, Stigma, Algerian Families, Simple Societies.